Impact of a webcast on nurses' delivery of tobacco dependence treatment. Issue 1 (5th July 2017) - Sarna, Linda; Bialous, Stella A; Wells, Marjorie; Brook, Jenny
Abstract : Aims and objectives: To evaluate an educational programme about nurses' role in tobacco dependence treatment, and its webcast component, on the long‐term impact of increasing the frequency of nurses' self‐reported changes in practice related to delivery of smoking cessation interventions. Background: Healthcare professionals' knowledge about evidence‐based tobacco dependence treatment using the 5As framework (Ask about tobacco use, Advise users to quit, Assess willingness to quit, Assist in making a quit plan and Arrange for follow‐up, including referral to a quitline) is essential to increase smoking cessation rates in the United States. Design: A 6‐month pre–post design. Methods: A convenience sample of nurses ( N = 283) from Kentucky and Louisiana was provided access to the webcast and printed toolkit. Responses from those who completed an online survey at baseline, and at 3 or 6 months postimplementation of the educational programme were included in an analysis of changes in the consistent (always/usually) delivery of the 5As plus referral to the quitline. Results: After 3 months, the intervention had a significant impact on increasing nurses' reports of consistently providing the 5As to patients who smoked, which was largely sustained at 6 months. Nurses who viewed the webcast were three times more likely to refer smokers to a quitline at 3 months; and four times more likely at 6 months than those who did not. Conclusions: An online educational programme, plus printed toolkit about tobacco dependence treatment increased nurses' delivery of smoking cessation interventions over time. This study provided preliminary evidence that including a webcast in a nurse‐targeted educational programme could significantly increase the proportion of nurses who referred smokers to a quitline beyond the benefit of access to printed materials and web‐based resources. Relevance to clinical practice: Distance learning is a feasible mechanism for enhancing nurses' involvement in tobacco dependence treatment and promoting evidence‐based clinical practice.